Answer:
A. [tex]\log _2\left(6\right)+\log _2\left(7\right)=\log _2\left(42\right)[/tex]
Step-by-step explanation:
To express [tex]\log _2\left(6\right)+\log _2\left(7\right)[/tex] as a single logarithm you must apply the log rule:
[tex]\log _c\left(a\right)+\log _c\left(b\right)=\log _c\left(ab\right)[/tex]
So,
[tex]\log _2\left(6\right)+\log _2\left(7\right)=\log _2\left(6\cdot \:7\right)[/tex]
Multiply the numbers: [tex]6\cdot \:7=42[/tex]
[tex]\log _2\left(6\right)+\log _2\left(7\right)=\log _2\left(42\right)[/tex]